2011
DOI: 10.1007/s11605-011-1637-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Radiotherapy Combined with Capecitabine Chemotherapy in Chinese Patients with Locally Advanced Rectal Cancer

Abstract: Preoperative chemoradiotherapy with capecitabine and RT appears to be a safe, well-tolerated, and effective neoadjuvant treatment modality for LARC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…It is noteworthy that our ypT0-2N0 downstaging rate compares favorably with other studies using capecitabine plus RT (ypT0-2N0 41.2–50%) [5, 12, 15, 20, 2325]. Furthermore, other indices of tumor response (T/N downstaging, pCR) are comparable to other studies (Table 4) [5, 12, 1526].…”
Section: Discussionsupporting
confidence: 84%
“…It is noteworthy that our ypT0-2N0 downstaging rate compares favorably with other studies using capecitabine plus RT (ypT0-2N0 41.2–50%) [5, 12, 15, 20, 2325]. Furthermore, other indices of tumor response (T/N downstaging, pCR) are comparable to other studies (Table 4) [5, 12, 1526].…”
Section: Discussionsupporting
confidence: 84%
“…In China, most patients diagnosed as T3 or T4 rectal cancer [ 9 ], which is characterized by large tumor size and involvement of rectal fascial layers, and which leads to significantly difficult dissection in the bloodless plane as well as more technically challenging for laparoscopic surgery than early rectal cancer. The rate for severe complication after laparoscopic surgery for advanced-stage rectal cancer has been reported to be 22.5%, whereas the rate for early-stage rectal cancer was 2% [ 10 , 11 ], which suggested that risk factors of severe complications for advanced rectal cancer is different from that for early-staged rectal cancer after laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,9,10,21,24,26 We have also found a posttreatment nodal involvement (30.7%) slightly higher than in other studies. 5,[8][9][10][11]14,24 total mesorectal excision was performed by the same senior surgical team 5 to 6 weeks after neoadjuvant treatment. sphincter preservation was achieved in 51 patients (60.2%) with low rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] on this basis, for locally advanced rectal cancer (laRC), neoadjuvant CRt followed by surgery is currently the preferred treatment option. 5,[13][14][15] adjuvant chemotherapy (Cht) is usually recommended, although controversy exists in patients who have been rendered node negative by preoperative treatment. 15,16 the multidisciplinary management of laRC has translated into a decrease in the rate of local failure.…”
mentioning
confidence: 99%